Assessing the regional policies of Italian regions in managing the Cesarean delivery phenomenon: a fractal analysis.: Fractal statistic and Cesarean section. - Indraccolo, Ugo; Bianchi, Beatrice; Borghi, Chiara; Greco, Pantaleo (Acta Biomedica Atenei Parmensis, 2021)
Objectives. Assessing the 2017 administrative data on Cesareans delivery in Italy by using fractal statistic.Methods. 2017 administrative data on Italian Cesarean deliveries are freely available as crude numbers and rates according to each Italian region, according to Italian health institute type and according to first or repeated Cesarean. As already reported, the Italian Cesarean delivery phenomenon is in relationship with hospital, regional, cultural perspectives in caring pregnancy and delivery. Fractal statistics can best assess the biocomplexity underlying the Italian Cesarean section phenomenon. Fractal shapes and self-organized criticality of the Cesarean section phenomenon for each Italian region were done. Fractal shapes were compared to find similarities by using global test of coincidence among regression lines. Results. In the regions where the health care institutes are more than a type, there are evanescent similar fractal shapes. Self-organized criticality assessment demonstrates that chaos is largely involved in Cesarean delivery phenomenon in all Italian regions and in Italy. The fractal images for each region are able to highlight the item causing the deviation from fractal shapes in each region. Conclusion. Fractal statistics could be used to compare regional or hospital policies in performing Cesareans, starting from Cesareans rates extracted from administrative data.